Abdominal tuberculosis can cause utero-cutaneous fistula following caesarean section - RC, Laxmi (Journal of General Practice and Emergency Medicine of Nepal, 2021)
A 30-year-old lady was presented with complaints of intermittent pus like blood mixed discharge during her menstruation. This was located at the midline incision below the umbilicus, following a seven month caesarean section. Magnetic resonance imaging (MRI) showed uterocutaneous fistula. A uterocutaneous fistula is a rare complication following caesarean section. This was the first case of utero cutaneous fistula which was reported in our hospital. The following procedures were carried out; laparotomy, total abdominal hysterectomy with left salpingooophorectomy. The histopathology report showed tuberculosis. After nine months of treatment with anti-tubercular drugs the patient has recovered and has no complaints.